Kids, Caregivers, and Cartoons: The Impact of Licensed Characters on Food Choices and Consumption. (April 2019) - Leonard, Bridget; Campbell, Margaret C.; Manning, Kenneth C.
This research examines effects of on-package licensed characters on children's and caregivers' choices of healthy and indulgent food and children's consumption amount. The authors propose that food liking exerts the greatest influence on children's choices and consumption, such that the impact of on-package characters will be limited to choices between equally liked options. Caregivers' choices are primarily influenced by their food goals for their children; thus, the impact of characters will likewise be limited to caregivers' within-category choices. Two experiments show that a character influences children's choices between two same-category options but not between indulgent and healthier options. A third experiment reveals that food liking influences amount consumed, while the presence of a character influences neither amount consumed nor food liking. Two additional experiments show that characters influence caregivers' choice between the same foods, but not between different food types or intention to purchase a food. The expanded framework for the effects of licensed characters—taking into account choice versus consumption, children versus caregivers, and healthy versus unhealthy foods—enhances understanding for consumers, practitioners, and policy makers.